2001
DOI: 10.1093/ndt/16.3.556
|View full text |Cite
|
Sign up to set email alerts
|

Resting energy expenditure in pre‐dialysis diabetic patients

Abstract: Metabolic disturbances of poorly controlled DM may account for the higher REE observed in the CRF diabetes group. The role of the apparently higher protein breakdown in this increased REE remains to be clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 26 publications
1
41
0
3
Order By: Relevance
“…However, in a study comprising 24 CKD diabetic patients and 24 CKD nondiabetic patients, the resting energy expenditure (64387963 and 560571318 kJ/day (15387230 and 13397315 kcal/day), respectively) was very similar to the energy intake estimated by 4-day food records (608671515 and 611671754 kJ/day (14547362 and 14617419 kcal/day), respectively). As the body mass index was indicative of overweight (26.874.7 and 25.873.8 kg/m 2 , respectively), this result suggests some degree of underestimation of energy intake (Avesani et al, 2001). Protein intake was indeed underestimated in the present study.…”
Section: Discussionsupporting
confidence: 42%
“…However, in a study comprising 24 CKD diabetic patients and 24 CKD nondiabetic patients, the resting energy expenditure (64387963 and 560571318 kJ/day (15387230 and 13397315 kcal/day), respectively) was very similar to the energy intake estimated by 4-day food records (608671515 and 611671754 kJ/day (14547362 and 14617419 kcal/day), respectively). As the body mass index was indicative of overweight (26.874.7 and 25.873.8 kg/m 2 , respectively), this result suggests some degree of underestimation of energy intake (Avesani et al, 2001). Protein intake was indeed underestimated in the present study.…”
Section: Discussionsupporting
confidence: 42%
“…Uremia per se and the dialysis procedure are associated with some metabolic derangements such as metabolic acidosis, insulin resistance and inflammation, that augment protein catabolism (Mitch et al, 1999) and could in turn contribute to the variations of REE. Accordingly, it has been shown that nondialysis CKD patients with poorly controlled diabetes (Avesani et al, 2001) and HD patients with severe hyperparathyroidism have increased REE. Inflammation is a highly prevalent condition among CKD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Posteriormente, trabalhos com objetivo semelhante, mas que empregaram metodologia mais adequada (grupos pareados por sexo e idade, e ajuste do GER pela massa corporal magra) mostraram resultados diferentes [15][16][17] . Na fase não dialí-tica da DRC, um estudo que avaliou o GER de indivíduos idosos (n=15, idade 60 anos) mostrou que ele se encontrava reduzido quando comparado ao de idosos saudáveis 17 .…”
Section: Gasto Energético De Repouso Na Doença Renal Crônicaunclassified
“…Ao compilar trabalhos que avaliaram o papel de comorbidades (diabetes Mellitus, hiperparatireoidismo secundário e condição inflamatória crônica) sobre o GER, observou-se que ele, nessas condições, encontrava-se aumentado em cerca de 12% a 23% 5,16,[21][22][23] . Vale mencionar ainda que o próprio procedimento de HD também é capaz de aumentar o gasto energético.…”
Section: Gasto Energético De Repouso Na Doença Renal Crônicaunclassified
See 1 more Smart Citation